Brain correlates of declarative memory atypicalities in autism: a systematic review of functional neuroimaging findings - Pierre Desaunay; Bérengère Guillery; Edgar Moussaoui; Francis Eustache; Dermot M. Bowler; Fabian Guénolé (Molecular Autism, 2023)
Highlights Brain correlates of memory processes in autism spectrum disorder display functional asymmetries. Greater reliance on left than right-hemisphere functioning. Greater reliance on posterior than anterior brain functioning. Greater reliance on ventral stream than dorsal stream functioning. These functional asymmetries may account for memory atypicalities in ASD.